Reimagining Philippine Revolution - Serrano, Isagani (Kasarinlan: Philippine Journal of Third World Studies; Vol 10 No 2 (1994): Rethinking the State and the Economy 2, 2008)
According to the popular democratic (PD) revolutionaries of the Philippines, socialism is not the cutting edge of revolution. Socialism cannot win the battle against capitalism if it does not undergo continuous rethinking and revision demanded by changing realities. What clearly sets socialism apart is its stress on equity and its social mode of appropriation of wealth and resources. However, its growth-oriented trajectory of organizing the economy does not fundamentally differ from that of capitalism; thus, it suffers from the same technological fixation that harms nature. Furthermore, the belief that armed struggle is necessary in order to wrest power from the ruling elite—a belief espoused by many armed socialist groups in the Philippines—is erroneous; armed struggle should serve the empowerment of unarmed millions who are involved in a whole range of revolutionary activities besides taking up arms. The legal struggle, meanwhile, offers a wider scope for popular participation and empowerment—its shortcomings may be addressed by armed struggle; reform and revolution feed on each other and form part of a continuum of giving power to people and communities.